PERSEPSI AKUNTAN PENDIDIK DI KOTA PADANG TERHADAP IDE PENGINTEGRASIAN MUATAN ETIKA DALAM KURIKULUM AKUNTANSI - Henri Agustin; Lili Anita (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
This research aims to describe perceptions of accounting lectures from 2 state universities in Padang (Universitas Negeri Padang and Universitas Andalas) about the idea integrating ethics into accounting curiculum. Data for this research were collected by using quessioner adopted from Fisher et al., (2005). As many as 42 quessioners (16 from UNP and 28 from UNAND) were returned back to the researchers, and then the collected data were analyzed using descriptive statistics tehniques. The research results proved that both accounting lectrures from UNP and UNAND were (1) stongly agree that ethical content should be embodied into accounting curriculum, (2) agree that ethical contents in accounting curriculum should be teached by a collaboration between accounting lectures and accounting practioners, (3) stongly agree that ethical conducts and moral obligations as an accountant were the main aspects that should be teached to accounting students, (4) agree that embodied ethical contents to every subjects in accounting curriculum was  the best way in integrated ethics to accounting students, and (5) strongly agree that the best learning methods in integrated ethics for accounting students were using critical review on ethics articels and  implementing those ethical values in every day life